IMPLEMENTASI GEMA DIGILIB 4.0: GAMIFIKASI LITERASI BERBASIS KEARIFAN LOKAL SEBAGAI MEDIA EDUKASI MASYARAKAT DESA RAKATEDA II, KECAMATAN GOLEWA BARAT KABUPATEN NGADA - Kaka, Pelipus Wungo; Ferdiansyah; Kadek Wirahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Student Organization Capacity Building Program (PPK Ormawa) through Gema Digilib 4.0 was implemented in Rakateda II Village as an effort to improve community digital literacy based on local wisdom. Problems faced by the community include low interest in reading, limited access to literacy materials, and low utilization of digital technology for educational activities. This program aims to improve the community's digital literacy skills while preserving local culture through the digitization of local wisdom-based content. The implementation method was carried out in a participatory manner through field surveys, observations, Focus Group Discussions (FGDs), and in-depth interviews with the community and village government. The program was implemented through pioneering, development, and independence stages which included the development of the Gema Digilib 4.0 platform, digital literacy training, development of gamification features, the formation of a village literacy community, and community mentoring. The program results showed an increase in community participation in digital literacy activities, increased interest in reading among children and adolescents, increased productive use of digital technology, and the digitization of local culture in Rakateda II Village as an effort to preserve culture. In addition, the formation of a village literacy community supports the sustainability of the program independently in the community. Thus, Gema Digilib 4.0 can be a solution for strengthening community-based digital literacy and sustainable local wisdom in rural areas.